Development and formulation of coolant and non-corrosive aerosol forming agent system - Zhang, Xiaotian (2015)
A newly synthesized non-corrosive and effective aerosol fire extinguishing agent together with an effective coolant for hot aerosol cooling were successfully prepared and their properties and working performances were studied and discussed. The new Stype aerosol forming agent which contains 12.2% potassium nitrate, 44.2% strontium nitrate, 8.0% magnesium powder, 17.5% alpha-lactose, 11.1% ammonium nitrate and 7% epoxy binder was formulated to replace the corrosive K-type aerosol forming agents that currently dominates the aerosol fire extinguishant market. The fire suppression time, combustion reaction, combustion velocity, aerosol phase composition, combustion residue composition, aging profile and corrosion performance of this newly synthesized S-type aerosol forming agent were studied and analyzed. This new S-type aerosol forming agent could extinguish a heptanes pan fire in less than 20s in a 1 m3 compartment and the discharged aerosol particles have surface resistivity larger than 20 MΩ which is the threshold insulation level for protecting the electrical devices and electronics according to the Aerosol Fire Extinguishing System, Part1: Condensed Aerosol Fire Extinguishing Device GA 499.1-2004 and GA 499.1-2010. Moreover, this is the first time in the research field of aerosol fire extinguishing agents that dynamic modeling of combustion temperature and pressure inside an aerosol forming agent canister were successfully achieved. During combustion, the temperature at the canister nozzle would rise to over 1000°C very quickly, thus a substantial cooling of the discharged aerosol using any coolant is compulsory. The simulation of the canister’s inner pressure and temperature distribution on the coolant geometry provides instructive information on coolant geometry design and packing pattern of coolant. A packing bed randomly packed with Φ 5 mm kaolinite-based spherical coolants was used to cool down the hot aerosol and its temperature was brought down from 1400°C to below 400°C without any additional coolant. The mass of coolants applied is equal to the mass of the newly synthesized aerosol forming agent and the performance of such kaolinite-based coolant is relatively better than other common coolants used for hot aerosol cooling. Properties such as yield stress, thermal conductivity, water activity as well as manufacturing process of kaolinite-based spherical granulate were studied and discussed. The composition for synthesizing the kaolinite-based coolant used in this study is as follows: 42.8% kaolinite powder, 38.8% water, 8.1% epoxy A&B glue, 10.2% ethyl cellulose, and the evaporation of the absorbed water in the kaolinite mineral plays a major role in hot aerosol cooling.